2003
DOI: 10.1007/s11746-003-0687-z
|View full text |Cite
|
Sign up to set email alerts
|

Physical analyses of gel‐like behavior of binary mixtures of high‐ and low‐melting fats

Abstract: Gel-like fat mixtures of high-melting (HM) and low-melting (LM) fats were formed by means of rapid cooling and subsequent heating. No "non-fat" ingredients such as emulsifiers, water, or waxes were added to the mixtures. The gel-like fats having solid fat content (SFC) values below 2.0 wt% formed crystal networks of HM-fats that entrapped the liquid oil fraction of LM-fats. In a search for optimal fat combinations exhibiting gel-like behavior, fully hydrogenated rapeseed oil with a high amount of behenic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 24 publications
3
37
0
Order By: Relevance
“…1, gel-like behavior was observed as reported previously (Higaki et al, 2003). In this case, small FHR-B crystals with dimensions of 10 lm were formed in the FHR-B/SFO liquid mixture at T c ¼ 20°C (Fig.…”
Section: Effect Of V Csupporting
confidence: 85%
See 3 more Smart Citations
“…1, gel-like behavior was observed as reported previously (Higaki et al, 2003). In this case, small FHR-B crystals with dimensions of 10 lm were formed in the FHR-B/SFO liquid mixture at T c ¼ 20°C (Fig.…”
Section: Effect Of V Csupporting
confidence: 85%
“…Our previous XRD study showed that the b 0 and b forms developed in the FHR-B/SFO liquid mixture at T c ¼ 20°C. In addition, the b 0 form transformed to the b form by solid-state transformation after subsequent heating from 20 to 38°C not by melt-mediation when V c was 1.5°C/min (Higaki et al, 2003). The crystals shown in Fig.…”
Section: Effect Of V Cmentioning
confidence: 93%
See 2 more Smart Citations
“…Gel with water as the liquid component in the continuous phase is called hydrogel, while gel with liquid oil in the continuous phase is called organogel. Although hydrogels have been mainly used for nursing care food, organogels have better properties than hydrogels, such as weak polarity, resilience, and viscoelasticity 22,23 . Therefore, we considered that an organogel could be used as an aggregating ingredient of minced food, and developed an adjusted gelatinous fat in order to promote bolus formation.…”
Section: Discussionmentioning
confidence: 99%